Penurunan (Waste) Pada Proses Pembuatan Rice Hulling Roll (RHR) dengan Pendekatan Lean Manufacturing - Mauluddin, Yusuf; Nawawi, Irfan Ahmad (Institut Teknologi Garut, 2025)
PT. ABC is a rubber processing manufacturing company that produces Rice Hulling Rolls (RHR).The company faces challenges in meeting its weekly production targets due to a bottleneck in the turning process. This study applies a lean manufacturing approach using Value Stream Mapping (VSM) and Value Analysis Tools (VALSAT) to identify waste.The analysis results indicate that the main bottleneck occurs during the setup time of the lathe machine, which impacts production delays. To address this issue, the Single-Minute Exchange of Die (SMED) method was implemented, reducing setup time from 20 minutes to 10 minutes. Additionally, a time and motion study improved the efficiency of the turning process from 140 seconds to 130 seconds per cycle. As a solution, a Standard Operating Procedure (SOP) was developed, including setup time optimization guidelines and the implementation of left–right hand mapping to enhance turning process efficiency. This implementation is expected to reduce waste, improve production efficiency, and bring production output closer to the set targets. These findings offer practical contributions to the application of lean manufacturing in the manufacturing industry, with implications for industrial management in optimizing production processes.